Rise of the alliance eaudiobook - Brown, Ryk (Frontiers Saga, 2015)
A new ally providing aid . . . An old ally joining the fight . . . Their resources growing with each passing day . . . Their homeworld finally on the road to recovery . . . Things finally seem to be coming together for Captain Scott and the Alliance as he takes his forces on the offensive. However, the Jung may in turn give him more trouble than he bargained for.